THU0334 Differences in the features of familial mediterranean fever among patients from europe as compared to those from the eastern mediterranean countries. (23rd January 2014) - Ozen, S.; Demirkaya, E.; Amaryan, G.; Koné-Paut, I.; Woo, P.; Uziel, Y.; Finetti, M.; Quartier, P.; Modesto, C.; Papadopoulou-Alataki, E.; Nielsen, S.; Hofer, M.; et al.
Abstract : Objectives: The aim of this study was to compare the phenotype and genotype characteristics of familial Mediterranean fever (FMF) in children from the eastern Mediterranean to those from Europe. Methods: We extracted all patients who were registered to the EUROFEVER database as FMF. The database includes demographic data, characteristics of disease episodes, molecular analysis, comprehensive list of signs/symptoms in 11 broad organs/systems, laboratory parameters, disease course, and outcome. Two experts independently reviewed extracted data (SO and, MG) and confirmed the diagnosis. Results: A total of 438 patients with FMF were collected from 23 different countries. Patients were divided into two groups according to their country of origin as those from the eastern Mediterranean region (Group I) (n=175) and those from Europe (Group II) (n=125). Group I included countries where FMF has a high prevalence such as Turkey, Israel, Armenia, Azerbaijan and Arabic countries of the eastern Mediterranean region. The mean age of disease onset was younger in Group I (3.9±3.3 years) compared to the European patients (6.9±10.7 years) (p=0.003) as was the age at diagnosis (6.6±3.5 years versus 11.9±2.9 years, respectively) (p<0.001). As expected consanguinity was more common among patients from the eastern Mediterranean region (p=0.009). Comparison of clinical manifestations showed that, oligoarthritis was more common among patients from the eastern Mediterranean (30.9%) as compared to those from Europe (8.8%) (p<0.001). Although abdominal pain distribution was similar in both groups, vomiting was present in 40.0% and 27.2% (p=0.022) of the patients and pleurisy was reported among 55.1% and 8.8% (p<0.001) in groups I and II, respectively. Although the most frequent gene mutation was M694V in both groups, this mutation was significantly higher among patients from the eastern Mediterranean region (59.2%) as compared to those from Europe (47.0%) (p=0.004). There was no significant difference between groups regarding response to colchicine (p=0.371). However, the follow up data indicated that complete remission with colchicine treatment was higher among the patients from the eastern Mediterranean (p=0.002). Conclusions: Our results show a number of phenotypic differences when FMF patients from the eastern Mediterranean were compared to those from Europe. Furthermore M694V was more frequent among patients from areas where FMF is frequent. The frequency of this mutation, the younger at onset, increased occurence of arthritis and pleurisy suggest a more severe disease in FMF patients from the eastern Mediterranean. Disclosure of Interest: None Declared